2008
DOI: 10.1021/pr800364d
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Metal Affinity Chromatography Revisited: pH/Acid Control toward High Selectivity in Phosphoproteomics

Abstract: Despite recent advances in instrumentation and analytical strategies for identification and quantitation of protein phosphorylation, a highly specific enrichment protocol is still a challenge in large-scale studies. Here, we report a simple pH/acid control method that addresses the poor specificity seriously criticized in IMAC. Detailed evaluation of the capture and release mechanism in IMAC revealed that pH, buffer and salt yield a complex interplay in enrichment of phosphopeptides, yet they play individual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 45 publications
5
121
0
Order By: Relevance
“…We compiled data from 13 independent proteomic studies (Amanchy et al, 2005;Brill et al, 2004;Cantin et al, 2008;Daub et al, 2008;Guo et al, 2008;Olsen et al, 2006;Pan et al, 2008;Rikova et al, 2007;Rush et al, 2005;Schlosser et al, 2006;Sui et al, 2008;Tao et al, 2005;Tsai et al, 2008), which identified 13 phosphorylated tyrosines in emerin (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We compiled data from 13 independent proteomic studies (Amanchy et al, 2005;Brill et al, 2004;Cantin et al, 2008;Daub et al, 2008;Guo et al, 2008;Olsen et al, 2006;Pan et al, 2008;Rikova et al, 2007;Rush et al, 2005;Schlosser et al, 2006;Sui et al, 2008;Tao et al, 2005;Tsai et al, 2008), which identified 13 phosphorylated tyrosines in emerin (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…They characterized over 2,360 nondegenerate phosphopeptides and 2,747 phosphorylation sites in the H1299 lung cancer cell line, showing that a low pH buffer increases the specificity of IMAC for phosphopeptides. The buffer composition was directly associated to the specificity and selectivity of the IMAC technique (Tsai et al, 2008;Jensen et al, 2007). Another important enrichment technique widely used is the metal oxide affinity chromatography (MOAC).…”
Section: Enrichment Of Phosphopeptides or Phosphoproteinsmentioning
confidence: 99%
“…Briefly, IMAC with Fe (III) or Ga (III) has been widely used to purify phosphopeptides, even though co-selection of non-modified sequences has been described as a major pitfall of the technique. Esterification of peptide carboxyl groups provides an increased specificity of phosphopeptide enrichment (Ficarro et al, 2002); alternatively, pH, buffer, and salt conditions have been tested to optimize the IMAC procedure (Tsai et al, 2008a). A double use of IMAC might be performed, at the protein and peptide levels, to increase phosphopeptide purification specificity (Cantin et al, 2008), and a fractionation step has also been widely performed before or after phosphopeptide enrichment on IMAC material: strong anion exchange (SAX) (Nuhse et al, 2004), SCX , hydrophilic interaction chromatography (HILIC) (Albuquerque et al, 2008;McNulty & Annan, 2008), Poros resins or graphite powder columns (Boeri Erba et al, 2005).…”
Section: Purification Of Phosphopeptidesmentioning
confidence: 99%